Borders, Geography, and Oligopoly: Evidence from the Wind Turbine Industry - Coşar, A. Kerem; Grieco, Paul L. E.; Tintelnot, Felix (The Review of Economics and Statistics, 2015)
Using a microlevel data set of wind turbine installations in Denmark and Germany, we estimate a structural oligopoly model with cross-border trade and heterogeneous firms. Our approach separately identifies border-related from distance-related variable costs and bounds the fixed cost of exporting for each firm. In the data, firms’ market shares drop precipitously at the border. We find that 40% to 50% of the gap can be attributed to national border costs. Counterfactual analysis indicates that eliminating national border frictions would increase total welfare in the wind turbine industry by 4% in Denmark and 6% in Germany.